THE IMPORTANCE OF THE TRADITIONS OF THE TEACHER AND DISCIPLE IN THE STUDY OF THE TRADITIONAL APPLIED ART OF BUKHARA (Intent Research Scientific Journal, 2023)
This scientific article provides for the study and analysis of the importance of the traditions of teachers and students in the study of the traditional applied art of Bukhara. Specific of Bukhara region during the article, using not only cultural historical monuments, but also artisan opportunities with the aim of continuing the traditions of the teacher and disciple in order to achieve economic efficiency through its history with a colorful and rich historical and cultural heritage and the development of traditional values in the province, it has been studied scientifically-theoretically and analytically that there will also be a significant emphasis on the further involvement of foreign investments in the organization of educational buildings, modernization of existing capacities and technological renewal in the continuation of new professions.